ANALISIS PERMAINAN MOBILE LEGENDS TERHADAP KECERDASAN EMOSINAL DI TINJAU DARI MATA PELAJARAN AGAMA ISLAM (KESABARAN) SISWA KELAS VI SEKOLAH DASAR - Muhammad Bagus Azmi; Abdul Rohman (UMSU, 2022)
Technology can have negative and positive impacts depending on how to use it, the result of technological advances that are so rapid there are online games which if not used properly will have a negative impact, someone will tend to get emotional if they lose in a game. The research was conducted with the aim of knowing the Mobile Legend game on students' emotional intelligence seen from Islamic religious subjects, the method used was a descriptive qualitative method using interview, observation and documentation techniques which were then analyzed so as to get results. The results obtained where students are more likely to have a sense of uncontrolled emotions, less social towards the surrounding environment and have negative thoughts.